Collective learning in social fields: Bourdieu, Habermas and critical discourse studies. (May 2016) - Forchtner, Bernhard; Schneickert, Christian
As societies have become increasingly differentiated and discourses have turned increasingly heterogeneous, field theory and critical discourse studies (CDS) have become ever more popular in the social sciences. Responding to this development, we propose a synthesis of Pierre Bourdieu's field theory and theories of collective learning inspired by Jürgen Habermas. Embedding this exploration within the framework of the discourse-historical approach (DHA) in CDS, we elaborate on how such a synthesis might look like by discussing the two traditions both vis-a-vis each other and vis-a-vis their current reception in the DHA. This synthesis is, finally, illustrated through the analysis of four types of blocked learning, four ways in which actual semiosis might block collective learning processes.